Fire Emergency Management Education To Improve The Preparedness Of Students At The Ta'dib Al-Syakirin Modern Islamic Boarding School - Susilawati; Putri Aswita Hani; Tri Sisty Annisa Sinaga; Juni Andini; Nuraini (Universitas Muhammadiyah Palu, 2026)
Fire is a high-risk disaster that occurs in educational environments, including Islamic boarding schools (pesantren) with compact facilities and high student mobility. This condition requires increasing students' knowledge and preparedness in facing emergency situations. This study aims to determine the effectiveness of fire emergency management education on improving students' knowledge and preparedness at the Ta'dib Al-Syakirin Modern Islamic Boarding School. This study used a quantitative method with a one-group pretest-posttest pre-experimental design. A total of 32 students were selected using a purposive sampling technique and underwent a series of pretests, education, and posttests. The results showed a descriptive increase in the knowledge and preparedness categories after being given education. All students achieved a good knowledge category on the posttest, and the good readiness category increased from 59.4% to 71.9%. However, the Wilcoxon test results did not show a significant difference in knowledge (p = 0.102) or readiness (p = 0.236). This study concluded that education has a positive impact in practice, but has not shown a statistically significant effect so that further training and periodic simulations are needed to strengthen student readiness.